Energy Profile and Building Energy Index (BEI) for Malaysian Public University: A Case Study of Universiti Tun Hussein Onn Malaysia (UTHM) - Muhammad Adib Afham Abdullah; Mohd Azahari Razali; Iman Fitri Ismail; Winardi Sani; Juntakan Taweekun (International Journal of Integrated Engineering, 2025)
Energy consumption is steadily increasing in emerging nations like Malaysia, driven by economic growth and the expansion of both commercial and residential sectors. The government has implemented various measures to ensure optimal and efficient building energy use. One such measure is the MS1525 standard, which evaluates a building’s energy efficiency as a benchmark for compliance with existing regulations. This study examines the Building Energy Index (BEI) of Universiti Tun Hussein Onn Malaysia (UTHM) at the Parit Raja, Batu Pahat campus to determine whether the buildings meet standard BEI requirements. The study’s objectives were achieved by collecting data on monthly energy consumption and selected buildings’ gross floor area, and then calculating the BEI to ensure accurate results. A preliminary audit involved a quick assessment of building and utility operations, site observations, and facility tours. Additionally, general audits provided more detailed insights into building operations, helping to identify the primary sources of energy consumption. According to the findings, the BEI for UTHM buildings ranges from 57 to 65 kWh/m²/year—significantly lower than the recommended BEI benchmark of 200 kWh/m²/year, as specified by Malaysian Standards and the guidelines for Malaysian green government buildings. However, fluctuations in the university’s energy consumption, influenced by factors such as semester breaks and the presence of multipurpose buildings, suggest the need for an adjusted method of BEI computation. A refined approach would provide more accurate BEI benchmarks tailored to public universities.